Digitalizacija Obzornika zdravstvene nege in njegova izposoja v knjižnicah v obdobju 2004-2010 - Dornik, Ema (Obzornik zdravstvene nege, 2013)
Introduction: The availability of the digitalised version of the journal will add to better recognition and visibility of the profession. The editorship of the Slovenian Nursing Review embarked on the project of digitalisation of the texts in their entirety. An enquiry was performed as to the changed extent andrate of library borrowing of the journal due to the project. Methods: The data on library borrowing were collected from the local database of the libraries included in the COBISS.SI system which were subscribed to at least one print copy of the journal. Included in the study were the libraries of the Faculty of Health Sciences, Ljubljana and the Faculty of Health Sciences, Maribor which present with the greatest number of items borrowed for the use at home and the library reading room. The statistical unit was the year of borrowing. The SPSS 20.0 statistical programme was used for statistical analysis of the sampled data. Results: Within the period from 2004 to 2010 thefollowing libraries lended the greatest number of the journal copies: Faculty of Health Sciences, Ljubljana (3765), Faculty of Health Sciences, Maribor (3147), College of Nursing Jesenice (331), University Library Maribor (217), Central Medical Library, University of Ljubljana (133). It was established that 91% of the borrowing fall into the first two years of the period studied, followed by the annual median drop in borrowing the Slovenian Nursing Review by 6,5 % and the Journal of the Slovenian Nursing Associationby 15,2 %. Both libraries noted a respective increase in 2007, namely, the Slovenian Nursing Review by 46.9% and the Journal of the SlovenianNursing Association by 11.8%. Other libraries documented no change in the lending/borrowing rate of the journal. Discussion and conclusion: Results of the study show a decline in the borrowing rates of the Slovenian Nursing Review and the Journal of the Slovenian Nursing Association, to all probabilty as a result of digitalisation of written sources. The state of affairs necessitates a free access to electronic version of the journal in order to gain greater popularity and support of the Slovenian nursing and midwifery care.
Keywords: digializacija; digital era trends; digitalna doba; izposoja; library borrowing; periodical publications; periodika